Exploring the Use of Nodality Based Information PolicyTools by Canadian Electoral Agencies - Craft, Jonathan (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2011)
Despite a healthy number of studies examining the motivations or voting practices of Canadians, little comparative work examines communications activities of electoral agencies. The following article maps out such activities through an assessment of nodality (information-based) policy tools use by four Canadian electoral agencies (Elections Canada, Elections Ontario, Elections BC, Elections Quebec). The paper begins by situating information‐based policy tools within the broader policy tools literature. Subsequently, such tools are then classified with respect to their relationship to policy making activities at the ‘front-end’ (agenda setting and policy formulation) and ‘backend’ (policy implementation and evaluation) of the policy cycle. Upon analysis, a variety of instrument mixes are detected with an overall shift from broad sweeping substantive instruments, such as mass information campaigns towards targeted approaches, to increased partnerships aimed at reaching specific cohorts with historically lower levels of voter participation. Furthermore, instrument mixes are found to vary jurisdictionally with respect to the adoption of newer Internet based tools versus traditional tools. In general, all four cases are found to frequently rely on both procedural and substantive information‐based policy tools related to ‘back-end’ policy-making activities.